Erratum to "Plasma biasing to control the growth conditions of diamond-like carbon" [Surface and Coatings Technology 201(2007) 4628-4632] (DOI:10.1016/j.surfcoat.2006.09.313) - Anders A. (2014)
[No abstract available]